High Performance Work Systems: A Necessity for Startups (Journal of Small Business Strategy (archive only), 2017)
New businesses are an important part of any economy, yet the key elements to achieve startup success are often unclear or up for debate. Attracting, selecting, and training employees are often critical activities for most startups. Research suggests that high performance work systems (i.e., a bundle of human resource practices) enhance organizational performance. However, we posit that most startups lack these systems at the onset, yet with minimal effort can establish a system to improve their likelihood of meeting their goals, enhancing capabilities, and ensuring long-term survival.